2005
DOI: 10.1256/qj.03.91
|View full text |Cite
|
Sign up to set email alerts
|

Upward and downward injection of Rossby wave activity across the tropopause: A new aspect of the troposphere–stratosphere dynamical linkage

Abstract: SUMMARYPropagation of zonally confined Rossby wave activity between the troposphere and lower stratosphere of the southern hemisphere during austral winter and spring of 1997 is studied, by using a wave-activity flux and refractive index, both defined for stationary Rossby waves on a zonally asymmetric time-mean flow. A particular event of large-scale quasi-stationary cyclogenesis in the troposphere is discussed, to which downward waveactivity injection from anticyclonic anomalies upstream that had developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…As in Nishii and Nakamura (2004), we neglected terms that contained the vertical deviation of N or because these terms are generally small. The refractive index s in Nishii and Nakamura (2004), which corresponds to K here, was derived under the assumption of nearly zonal basic flows.…”
Section: ͑1͒mentioning
confidence: 99%
See 2 more Smart Citations
“…As in Nishii and Nakamura (2004), we neglected terms that contained the vertical deviation of N or because these terms are generally small. The refractive index s in Nishii and Nakamura (2004), which corresponds to K here, was derived under the assumption of nearly zonal basic flows.…”
Section: ͑1͒mentioning
confidence: 99%
“…As in Nishii and Nakamura (2004), we neglected terms that contained the vertical deviation of N or because these terms are generally small. The refractive index s in Nishii and Nakamura (2004), which corresponds to K here, was derived under the assumption of nearly zonal basic flows. We established an assumption that the meridional component of the basic geostrophic wind is smaller than the zonal component (| g | K | u g | ) and that zonal deviation of q is smaller than the meridional derivation (| q x | K | q y |).…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the traditional application of zonally averaged diagnostics to troposphere-stratosphere communication may be misleading. In a follow-up to their study, Nishii and Nakamura (2005) presented evidence showing that a local vertical waveguide could also serve as a conduit for the local injection of stratospheric wave activity into the troposphere, perhaps providing an energy source for the local enhancement of tropospheric disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…This equation is often used to represent the mean-flow properties with respect to the propagation of stationary Rossby waves (e.g., Nishii and Nakamura 2005;Iwao and Takahashi 2008). Figure 2a shows the climatological geopotential height at 100 hPa.…”
Section: Climatological Fieldsmentioning
confidence: 99%